2019
DOI: 10.1016/j.biomaterials.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic nanoparticle delivery enhances the anticancer efficacy of a TLR7 ligand via local immune activation

Abstract: Although immunotherapy shows great promise for the long-term control of cancer, many tumors still fail to respond to treatment. To improve the outcome, the delivery of immunostimulants to the lymph nodes draining the tumor, where the antitumor immune response is initiated, is key. Efforts to use nanoparticles as carriers for cancer immunotherapy have generally required targeting agents and chemical modification of the drug, and have unfortunately resulted in low delivery and therapeutic efficiency. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…An amphiphilic gold nanoparticle 5 nm in size coated with 1-octanethiol and 11mercaptoundecanesulfonic acid was used to deliver a TLR7 ligand to tumor draining lymph nodes to act as an immunostimulant [150]. Nanoparticles were administered subcutaneously and caused local immune activation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An amphiphilic gold nanoparticle 5 nm in size coated with 1-octanethiol and 11mercaptoundecanesulfonic acid was used to deliver a TLR7 ligand to tumor draining lymph nodes to act as an immunostimulant [150]. Nanoparticles were administered subcutaneously and caused local immune activation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A delivery system composed of gold nanoparticles of 5 nm in diameter coated with an amphiphilic shell was developed, which allowed loading of resiquimod through non-specific adsorption. After subcutaneous injection of these resiquimod-loaded particles into tumorbearing mice, they accumulated in the tumor-draining lymph nodes where they led to activation of the dendritic cells in situ causing a cytotoxic T-cell response 61 . This treatment completely blocked the growth of the large tumor and extended the survival of the mice much more than the free drug 61 .…”
Section: Novel Drug Delivery Systems For Tlr and Rlr Agonistsmentioning
confidence: 99%
“…After subcutaneous injection of these resiquimod-loaded particles into tumorbearing mice, they accumulated in the tumor-draining lymph nodes where they led to activation of the dendritic cells in situ causing a cytotoxic T-cell response 61 . This treatment completely blocked the growth of the large tumor and extended the survival of the mice much more than the free drug 61 . Thus, the delivery of resiquimod to the tumor-draining lymph node, which is the site of initiation of the immune response against the tumor, was highly effective for triggering an anti-tumor response.…”
Section: Novel Drug Delivery Systems For Tlr and Rlr Agonistsmentioning
confidence: 99%
“…Kasturi et al have shown a synergistic effect of combining MPLA and R837 in PLGA nanoparticles on antibody production [ 101 ]. Many more examples exist of encapsulating adenine and imidazoquinoline TLR agonists into nanocarriers [ 98 , 102 , 103 ]. Fewer studies have been performed on the delivery of guanosine analogs such as 7-thia-8-oxoguanosine (TOG) and loxoribine (Fig.…”
Section: Pattern Recognition Receptor Agonistsmentioning
confidence: 99%